Service quality and customer satisfaction: experience of customers in postal service / Siti Rapidah Omar Ali and Siti Naemah Abd Hakim Amir - Omar Ali, Siti Rapidah; Abd Hakim Amir, Siti Naemah (Universiti Teknologi MARA, Perlis, 2020)
Providing great quality services is essential for a sustainable competitive advantage in today's aggressive business environment. An organisation's success could be positively influenced by customer satisfaction. This study has attempted to examine the relationship between service-quality elements towards customer satisfaction. The modified SERVQUAL model by Parasuraman et al. has been used to measure four servicequality dimensions. Quantitative method is used for data collection in this research. A set of a selfadministered questionnaire focused on customers of Pos Malaysia Centre in Kuala Terengganu was distributed and has collected a convenience sample of 322 Pos Malaysia customers. Pearson's correlation analysis has revealed that all the four service-quality elements are positively associated with customer satisfaction with a moderate correlation. All the hypotheses of the study are also supported. Responsiveness and reliability have been discovered to influence customer satisfaction most compared to the other elements. Therefore, these findings have suggested that service industries, particularly postal services, should cultivate the key service-quality elements thoroughly in order to enhance customer satisfaction without overlooking the remaining dimensions.